1992
DOI: 10.1126/science.257.5067.223
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry of Bulk Hydrogen: Reaction of Hydrogen Embedded in Nickel with Adsorbed CH 3

Abstract: Studies in heterogeneous catalysis have long speculated on or have provided indirect evidence for the role of hydrogen embedded in the catalyst bulk as a primary reactant. This report describes experiments carried out under single-collision conditions that document the distinctive reactivity of hydrogen embedded in the bulk of the metal catalyst. Specifically, the bulk H atom is shown to be the reactive species in the hydrogenation of CH(3) adsorbed on Ni(111) to form CH(4), while the H atoms bound to the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
143
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(145 citation statements)
references
References 12 publications
2
143
0
Order By: Relevance
“…Recently, there has been increased awareness of the role of subsurface solutes in bulk-like model catalysts (Pd, Cu, etc.) by recognizing, for example, that carbon in the bulk and the subsurface, usually considered ''frozen,'' actually changes the structure of the surface and even participates in heterogeneous catalysis [55][56][57][58]. Our findings suggest that similar effects may be even more pronounced in nanoparticles, capable of forming mixed metal-carbon structures that have no bulk equivalent and give rise to extremely high solute solubilities.…”
mentioning
confidence: 55%
“…Recently, there has been increased awareness of the role of subsurface solutes in bulk-like model catalysts (Pd, Cu, etc.) by recognizing, for example, that carbon in the bulk and the subsurface, usually considered ''frozen,'' actually changes the structure of the surface and even participates in heterogeneous catalysis [55][56][57][58]. Our findings suggest that similar effects may be even more pronounced in nanoparticles, capable of forming mixed metal-carbon structures that have no bulk equivalent and give rise to extremely high solute solubilities.…”
mentioning
confidence: 55%
“…11,12 Subsurface and bulk H could act as spectators modifying the electronic structure of the metal surface and thus its catalytic activity, 31 or act as a direct reactant in the hydrogenation reaction. 7 Compared to surface H, subsurface H in the octahedral site (O h ) of Ni(111) -directly underneath a surface fcc site-is metastable, with a binding energy of -2.19 eV. This metastable subsurface H can be prepared at low temperatures by exposure of the surface to atomic hydrogen followed by collision-induced recombinative desorption to remove the surface bound H under UHV conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Independently, Ni has been found to be a good catalyst for hydrogenation of hydrocarbons, whereby the presence of bulk and/or subsurface hydrogen played a special role in the observed reactivity. [7][8][9][10] In particular, it has been suggested that bulk and/or subsurface H exhibits unique reactivity in the heterogeneously catalyzed hydrogenation of hydrocarbons, such as methyl, ethylene and acetylene, on Ni(111). [7][8][9][10][11][12][13][14] For example, in seminal work by Ceyer et al, 7 it was unambiguously demonstrated that subsurface H is the reactant for hydrogenation of methyl radical to methane on Ni(111), whereas surface H is unreactive.…”
Section: Introductionmentioning
confidence: 99%
“…For a Ni(111) surface it was previously shown by Johnson et al that recombinative desorption of adsorbed methyl groups occurs exclusively with hydrogen atoms present in the bulk of the Ni crystal. 24 Bulk D-atoms were prepared by exposing the Ni(111) surface to a flux of D-atoms and subsequent bombardment of the surface with Xe-atoms. This causes recombinative desorption of surface bound D-atoms but leaves the subsurface D-atoms in place.…”
Section: Bond Selectivity In Gas-surface Reactionsmentioning
confidence: 99%